Política monetária sob restrição fiscal: uma análise do caso brasileiro - Jesus, Diego Pitta de (2018)
The aim of this paper is to analyze the effects of monetary policy shocks under fiscal restraint. For this, a DSGE model calibrated for the Brazilian economy was developed that includes restrictions on aggregate and disaggregated government spending (government consumption, social transfers and housing subsidy). In addition, simulations were carried out taking into account the Constitutional Amendment 95/2016 (EC 95) and two other alternative fiscal rules. The results indicated that the more austere the fiscal policy the lower the public debt response the interest rate increases. In addition, the exercises that took into account the EC 95 showed that this has worse results, from the point of view of response of fiscal variables to the monetary shocks than the other rules. On the other hand, EC 95 generated a higher level of aggregate welfare for the same shock when compared to the other fiscal rules.